Nonlinear Oscillations of Magnetization in a Tangentially Magnetized Ferromagnetic Film Resonator - R. V. Haponchyk; E. Lähderanta; A. B. Ustinov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Resonators based on epitaxially grown single-crystal films of yttrium iron garnet are used in various applications of microwave electronics. It is known that with increasing of microwave power incident on a resonator, various nonlinear effects begin to manifest themselves. There are: bistability effect, nonlinear frequency shift, nonlinear damping, etc. By now, the listed nonlinear effects have been quite good studied experimentally. Previously, when describing oscillations of various dynamical systems, the nonlinear damping and the nonlinear frequency shift were usually considered separately. At the same time, it was known that, when studying nonlinear magnetization oscillations in ferromagnetic film resonators with an increase in oscillation amplitude, these effects could occur simultaneously.Aim. Development of a model of magnetization oscillations taking into account the nonlinear frequency shift and nonlinear damping, as well as its experimental justification for a ferromagnetic film resonator.Materials and methods. The development of the model was carried out by the method of slowly varying amplitudes. An experimental study was carried out with a ferromagnetic film resonator. For the measurements, we used Rohde & Schwarz ZVA 40 vector network analyzer. We measured the frequency dependence of the reflection coefficient of the microwave signal from the resonator.Results. A model of nonlinear magnetization oscillations was developed taking into account both a nonlinear frequency shift and a nonlinear attenuation. The resonance curves were experimentally measured at various levels of the microwave power incident on the resonator. It was shown that nonlinear damping limits the nonlinear frequency shift of the magnetization oscillations in a tangentially magnetized ferromagnetic film resonator.Conclusion. The developed model adequately describes behavior of the resonance curves of ferromagnetic film resonators at high microwave power levels. The nonlinear damping leads to broadening of the resonance curves, thereby increasing losses. This effect also increases the reflection coefficient of the microwave signal from the resonator.